2020
DOI: 10.1016/j.phytochem.2020.112457
|View full text |Cite
|
Sign up to set email alerts
|

Highly different flavonol content explains geographic variations in the UV reflecting properties of flowers of the corn poppy, Papaver rhoeas (Papaveraceae)

Abstract: Papaver rhoeas, the corn poppy, is a very common weed in cereal fields all over the world. Its flowers generally display a bright red coloration, but their reflectance in the ultraviolet (UV) wavelength range varies geographically. Whereas the UV reflectance of East Mediterranean flowers is minor, that of Central European ones is substantial. By comparing the pigmentation of the differently reflecting flowers, we found that only East Mediterranean flower petals contain high amounts of UV absorbing flavonol gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Our results revealed a geographic cline of floral UV reflection in P. rhoeas that also correlates with a gradient of higher UV radiation toward the Mediterranean [49]. When red poppies are cultivated in Central Europe from seeds collected in the East Mediterranean, they develop petals with varying UV-reflecting patterns, i.e., petals with low UV reflectance, petals with substantial UV reflectance, and petals with intermediate patterns consisting of areas with low and substantial UV reflectance [35]. This variability indicates that in native populations of P. rhoeas, the synthesis of UV-absorbing pigments is influenced by environmental factors and suggests that its spread from the East Mediterranean westward into Europe could have triggered the occurrence of flower-color-polymorphic populations such as the ones observed in the North Mediterranean.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our results revealed a geographic cline of floral UV reflection in P. rhoeas that also correlates with a gradient of higher UV radiation toward the Mediterranean [49]. When red poppies are cultivated in Central Europe from seeds collected in the East Mediterranean, they develop petals with varying UV-reflecting patterns, i.e., petals with low UV reflectance, petals with substantial UV reflectance, and petals with intermediate patterns consisting of areas with low and substantial UV reflectance [35]. This variability indicates that in native populations of P. rhoeas, the synthesis of UV-absorbing pigments is influenced by environmental factors and suggests that its spread from the East Mediterranean westward into Europe could have triggered the occurrence of flower-color-polymorphic populations such as the ones observed in the North Mediterranean.…”
Section: Discussionmentioning
confidence: 54%
“…The low UV reflectance of the Mediterranean poppies is presumably caused by UV-absorbing pigments, the concentration of which, in Central European poppies, is severely diminished [ 35 ]. Pigments responsible for floral UV absorption, such as flavonoids, are also known for their protective effect against attack by herbivores [ 36 , 37 , 38 ] and photo damage caused by UV radiation [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the presence of certain pigments in flowers may not only act to attract pollinators but also protect against environmental factors such as UV radiation, drought, temperature, or herbivory (Koski et al, 2020; Narbona et al, 2021). UV‐absorbing flavonoids are pigments that, alone or in combination with other pigments, are commonly accumulated in floral guides or even in the whole petal and produce flower colour spectra with low or no reflectance in the UV region (Dudeck et al, 2020; Narbona et al, 2021). These pigments have been shown to increase plant fitness in several ways, such as protecting pollen from UV irradiance or as herbivory deterrents (Koski & Ashman, 2015; Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…absorbing flavonoids are pigments that, alone or in combination with other pigments, are commonly accumulated in floral guides or even in the whole petal and produce flower colour spectra with low or no reflectance in the UV region (Dudeck et al, 2020;Narbona et al, 2021). These pigments have been shown to increase plant fitness in several ways, such as protecting pollen from UV irradiance or as herbivory deterrents (Koski & Ashman, 2015;Zhang et al, 2013).…”
Section: Colour Signals Strategies Improving Detection By Hymenoptera...mentioning
confidence: 99%
“…Despite the long interest in betalain pigments, they have been mostly studied in a few model species and much remains to be elucidated with respect to their diversity and biosynthetic and regulatory pathway. Evidence has accumulated about the variability of pigment content in flowers in response to abiotic stress along geoclimatic gradients (Koski and Ashman, 2016;Dudek et al, 2020). The variability in pigment composition revealed by our results points at Cisthanthe as suitable models to study betalain biosynthesis, as well as their adaptive role under extreme environments.…”
Section: Discussionmentioning
confidence: 54%